Alcohol and tobacco use in a tuberculosis treatment cohort during South Africa’s covid-19 sales bans: A case series - Myers-Franchi, Bronwyn; Carney, T.; Rooney, J.; Malatesta, S.; White, L.F.; Parry, C.D.H.; Bouton, T.C.; Ragan, E.J.; Horsburgh, C.R.; Warren, R.M.; Jacobson, K.R. (MDPI, 2021)
Background: South Africa temporarily banned alcohol and tobacco sales for about 20 weeks during the COVID-19 lockdown. We described changes in alcohol and tobacco consumption after implementation of these restrictions among a small number of participants in a tuberculosis treatment cohort.